Preliminary aerothermal design of axial compressors - Piscopo, Giovanni (Cranfield University, 2013)
This dissertation documents a compressor preliminary design study conducted by the author in fulfilment of his MSc thesis requirements. The compressor is intended for a new development engine within the 20Klbf thrust category, planned to be used on a short-haul aircraft, namely the ERJ-190. A market research suggests that there exists a definite opportunity for a commercially profitable engine within this thrust class. Furthermore, the proposed new engine is projected to outperform current production engines on critical issues such as fuel efficiency and operability. By and large, the objectives of this work have been achieved and a compressor design and layout is suggested, which matched or exceeded all the initial requirements. The quality of the results from this study are thought to be of sufficient detail to allow a further, more detailed development study to resolve some subtle pending issues. It is expected that, some compressor stages may have to be altered slightly during detailed design to augment their performance and ease of manufacture and assembly. Throughout this study, the importance of the compressor design figure of merits, pertaining to a short haul engine, has been outlined and their interaction on the design process is well documented. Furthermore, some rather unorthodox objectives such as compressor performance retention and reliability have been discussed. The author approached these subjects in an innovative way due to the limited non-proprietary knowledge available on these issues, especially considering their implications within preliminary design. Furthermore, the author developed and tested a new preliminary turbomachinery design code, named Turbodev, which can be used as an aid in future compressor design endeveours. Turbodev can handle most types of compressor layouts and generates an overall aerodynamic assessment of the turbomachinery performance. In conclusion; this documentation and the associated literature review aim to provide the reader with an overview of the work done and yield a better understanding of the decisions that face any design bureau when developing a new or modified engine component.
Keywords: short-haul; compressor layout; figure of merits; Turbodev; compressor reliability; performance retention